PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS DAN KETERAMPILAN SOSIAL SISWA SMP NEGERI DI KOTA BANDUNG - Ani Minarni (Study Program of Mathematics Education of Unimed Postgraduate Program, 2012)
This article is the result of the research about the effect of problem-based learning (PBL) towards mathematical understanding ability (MUA) and social skills (SS). The population of the research is all of the studeant of public middle level school in Bandung. The sample is taken by simple stratified random sampling technique.The instrument used in this research are a set of essay test to measure mathematical understanding ability and a set of questionaire to measure the students’ social skills. One-way Anova and two-way Anova are used to analyze the data. The research findings are: (1) PBL gives significant effect towards MUA based on learning approach (2) There’s no interaction between PBL and MPK towards MUA; (3) PBL gives significant effect towards SS based on learning approach (4) There’s no interaction between PBL and MPK towards SS, so is between learning approach and school level, (5) The correlation between MUA and SS is not strong enough.